The effect of long-term azithromycin treatment on the respiratory microbiota of HIV-infected children with chronic lung disease - Abotsi, Regina Esinam (Department of Molecular and Cell Biology, 2023)
Background: HIV-associated chronic lung disease (HCLD), predominantly obliterative bronchiolitis, affects more than 30% of perinatally HIV-infected children in Sub-Saharan Africa. There are currently no treatment guidelines for HCLD. A recent clinical trial demonstrated that long-term azithromycin therapy reduced the frequency of acute respiratory exacerbations and all-cause hospitalisations in HCLD patients. However, our understanding of the microbial determinants of HCLD and how azithromycin therapy modulates these determinants is limited. This study investigated the carriage and antibiotic resistance of common potentially pathogenic bacteria in the respiratory tract of children living with HIV (CLWH) with (CLD+) and without HCLD (CLD-). It also evaluated the impact of long-term azithromycin therapy on the prevalence and antibiotic resistance of selected bacterial species in the respiratory tract of CLD+ CLWH. Thirdly, the study assessed the effect of azithromycin on the sputum bacteriome of participants. Finally, the persistence of the bacteriological impact of azithromycin, six months post-intervention, was also investigated. Methods: This study was nested within the Bronchopulmonary Function in Response to Azithromycin Treatment for Chronic Lung Disease in HIV-Infected Children (BREATHE) trial, a multi-site, double-blind, placebo-controlled, individually randomised trial (ClinicalTrials.gov Identifier: NCT02426112) that investigated the efficacy of azithromycin therapy in children and adolescents aged 6 to 19 years with HCLD (defined as forced-expiratory volume per second (FEV1) z-score < −1 without reversibility post-bronchodilation with salbutamol) in Zimbabwe and Malawi. Paired nasopharyngeal swabs and sputa were collected at baseline, 48 and 72 weeks from participants randomised to receive 48 weeks of once-weekly oral azithromycin or placebo and followed post- intervention until 72 weeks from baseline. Baseline samples were also collected from a comparison group of CLD– participants frequency matched for site, age (6-12 and 13-19 years), and duration of antiretroviral therapy use (6 months to < 2 years and ≥ 2 years). All samples were cultured for Streptococcus pneumoniae, Staphylococcus aureus, Haemophilus influenzae and Moraxella catarrhalis and other Gram-negative bacilli. Antibiotic susceptibility testing was conducted on the isolated bacteria using the disk diffusion method. Total bacterial load and bacteriome profiles of the CLD+ sputum samples were determined using 16S rDNA quantitative (q)PCR and V4 region amplicon sequencing. Risk factors for bacterial carriage were identified using questionnaires and analysed using multivariate logistic regression. Bacterial carriage over the three visits, associations between clinical and socio-demographic factors, and bacteriome diversity were determined by mixed effect models with participants as a random effect. Antibiotic resistance between arms was compared using Fisher's exact test. Results: Between June 2016 and September 2018, a total of 410 participants (336 CLD+, 74 CLD-) were enrolled (median age, 15 years [IQR = 13–18]). S. pneumoniae and M. catarrhalis carriage in the nasopharyngeal swabs were higher in CLD+ than in CLD- children: 46% (154/336) vs 26% (19/74), p = 0.008; and 14% (49/336) vs 3% (2/74), p = 0.012, respectively. S. pneumoniae isolates from the nasopharyngeal swabs of CLD+ children were more likely to be non-susceptible to penicillin than those from CLD- children (36% [53/144] vs 11% [2/18], p = 0.036). Overall, methicillin-resistant S. aureus was uncommon [4% (7/195)]. In multivariate analysis, key factors associated with nasopharyngeal bacterial carriage included having HCLD (S. pneumoniae: adjusted odds ratio (aOR) 2 [95% Confidence Interval (CI) 1.1–3.9]), younger age (S. pneumoniae: aOR 3.2 [1.8–5.8]), HIV viral load suppression (S. pneumoniae: aOR 0.6 [0.4–1.0], S. aureus: 0.5 [0.3–0.9]), stunting (S. pneumoniae: aOR 1.6 [1.1–2.6]) and male sex (S. aureus: aOR 1.7 [1.0–2.9]). Key factors associated with sputum bacterial carriage included the Zimbabwean study site (S. pneumoniae: aOR 3.1 [1.4– 7.3], S. aureus: 2.1 [1.1–4.2]), being on ART for a longer period (S. pneumoniae: aOR 0.3 [0.1–0.8]), and sampling in hot compared to rainy season (S. pneumoniae: aOR 2.3 [1.2–4.4]). Of the 347 (174 azithromycin, 173 placebo) CLD+ participants included in the main trial (median age 15 years [IQR = 13–18], females 49%), nasopharyngeal carriage was significantly lower in the azithromycin (n = 159) compared to placebo (n = 153) arm for S. pneumoniae (18% vs 41%, p < 0.001), H. influenzae (7% vs 16%, p = 0.01), and M. catarrhalis (4% vs 11%, p = 0.02) at 48 weeks. S. pneumoniae resistance to azithromycin (62% [18/29] vs 13% [8/63], p < 0.0001) or tetracycline (60% [18/29] vs 21% [13/63], p < 0.0001) were also higher in the azithromycin arm at 48 weeks. Carriage of S. aureus resistant to azithromycin (91% [31/34] vs 3% [1/31], p < 0.0001), tetracycline (35% [12/34] vs 13% [4/31], p = 0.05) or clindamycin (79% [27/34] vs 3% [1/31], p < 0.0001) was also significantly higher in the azithromycin arm at 48 weeks and persisted at 72 weeks. Similar findings were observed for sputa. Placebo allocation was associated with decreased likelihood of azithromycin-resistant S. pneumoniae or S. aureus carriage in the nasopharyngeal swabs or sputum. Forty-eight weeks of azithromycin reduced sputum bacterial load vs placebo arm (16S rDNA copies/μl in log10, mean difference and CI of azithromycin vs placebo -0.54 [-0.71; -0.36]). Shannon alpha diversity remained stable in the azithromycin arm but declined in the placebo arm between baseline and 48 weeks (3.03 vs 2.80, p = 0.04, Wilcoxon paired test). Bacterial community structure changed in the azithromycin arm at 48 weeks compared with baseline (PERMANOVA test p = 0.003) but resolved at 72 weeks. The relative abundances of genera previously associated with HCLD decreased in the azithromycin arm at 48 weeks compared with baseline, including Haemophilus (17.9% vs 25.8%, p < 0.05, ANCOM ω = 32) and Moraxella (1% vs 1.9%, 47, p < 0.05, ANCOM ω = 47). This reduction was sustained at 72 weeks relative to baseline. Lung function (FEV1z-score) was negatively associated with bacterial load (linear mixed effect model coefficient, [CI]: -0.09 [-0.16; -0.02]) and positively associated with Shannon diversity (0.19 [0.12; 0.27]). The relative abundance of Neisseria (coefficient, [standard error]: (2.85, [0.7], q = 0.01), and Haemophilus (-6.1, [1.2], q < 0.001) were positively and negatively associated with FEV1z, respectively. An increase in the relative abundance of Streptococcus from baseline to 48 weeks was associated with improvement in FEV1z-score (3.2 [1.11], q = 0.01), whilst an increase in Moraxella was associated with a decline in FEV1z-score (-2.74 [0.74], q = 0.002). Conclusions: CLD+ children were more likely to carry M. catarrhalis and S. pneumoniae, including penicillin-non-susceptible S. pneumoniae strains, than CLD- children. Long-term azithromycin reduced carriage of S. pneumoniae, H. influenzae and M. catarrhalis but promoted antibiotic resistance in S. pneumoniae and S. aureus; antibiotic-resistant S. aureus persisted at 72 weeks, six months after treatment completion. Azithromycin also reduced total bacterial load and modulated the sputum bacteriome away from potentially pathogenic taxa, which may explain the beneficial effect of azithromycin in reducing acute pulmonary exacerbations in this population. The risk of drug resistance should be considered during long-term azithromycin use and the clinical significance of this resistance and the benefits of azithromycin use beyond 48 weeks needs further investigation.